IBD 6 What to do with a saxophone penis: a case report. (12th September 2022) - Chan, Joseph; Spray, Christine
Abstract : Introduction: A saxophone penis is extremely rare in children. This occurs when the penis gets twisted along its long axis, giving the appearance resembling a saxophone ( figure 1 ). The causes are not well described in Paediatrics. In the adult literature chronic lymphatic obstruction or infection are the main causes. Aim: To present an interesting case and five-year timeline of a patient affected by a saxophone penis. Subjects and Methods: A normally fit and well nine-year old boy presented to A&E and was seen by the surgeons in July 2016 with a five-day history of pain and swelling of his penis. The initial impression was balanitis with cellulitis; he received oral and topical antibiotics. He was followed up by the surgical team and referred as an outpatient and reviewed by Paediatric Gastroenterology in October 2016. Skin punch biopsies of the genitalia showed non-caseating granulomas. His initial OGD and ileocolonosocpy were macroscopically and histologically normal. He was diagnosed with genital Crohn's disease. He was sequentially treated with sulfasalazine, oral prednisolone and azathioprine but continued to complain of pain, swelling and sensitivity and was started on adalimumab in July 2017. There was a good response physically and after 18 months this was stopped. Psychologically he developed issues with chronic pain, sensitivity and school avoidance. One year after stopping anti-TNF therapy he developed loose stools and had poor weight progression. A repeat endoscopy revealed aphthous ulcers in D2 with active inflammation in the duodenum and colon with histology showing granulomas. His response to exclusive enteral nutrition and oral prednisolone was suboptimal and he was re-started on adalimumab in February 2021. He is now 14 years old and on dual therapy with azathioprine and 2 weekly adalimumab. Summary: We present an interesting case of an adolescent male who initially presented when nine years old with a saxophone penis (genital Crohn's disease). After three and a half years he developed luminal Crohn's disease. Conclusion: Crohn's disease affecting the genitalia is a rare and challenging diagnosis both physically and psychologically. The terminology used varies by specialty with commonly recognised terms being; 'genital Crohn's', 'anogenital granulomatosis' and 'metastatic Crohn's Disease'. Early MDT discussions including psychology support should be initiated and early anti-TNFs considered. Awareness with our colleagues needs to be raised to improve and streamline local and national referral processes to avoid delays in initiating treatment.